2019
DOI: 10.18203/issn.2455-4529.intjresdermatol20190984
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical study on homologous autoinoculation in anogenital wart

Abstract: <p class="abstract"><strong>Background:</strong> Ano-genital wart, an infection of the anal and genital mucosa with their adjoining area is caused by human papilloma virus. Genital warts pose a bigger challenge, because of the lack of cell mediated immunity and its propensity to relapse and the reluctance of patients to consult a physician. The main aim of our study is to determine whether autoinoculation is effective in treatment of ano-genital warts.</p><p class="abstract"><s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…Since then, four open‐labeled studies from India reported response to autoinoculation therapy in 65% to 88% of patients with verruca vulgaris within a follow‐up period of 3 to 6 months 7‐10 . Two studies of autologous implantation on genital warts showed a response rate of 60% to 70% 11,12 . In our study, complete response was seen in 65% patients.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Since then, four open‐labeled studies from India reported response to autoinoculation therapy in 65% to 88% of patients with verruca vulgaris within a follow‐up period of 3 to 6 months 7‐10 . Two studies of autologous implantation on genital warts showed a response rate of 60% to 70% 11,12 . In our study, complete response was seen in 65% patients.…”
Section: Discussionsupporting
confidence: 56%
“…[7][8][9][10] Two studies of autologous implantation on genital warts showed a response rate of 60% to 70%. 11,12 In our study, complete response was seen in 65% patients. Previous studies have found that periungual warts are difficult to treat/cure because of the involvement of the nail and/or nail bed leading to the possibility of deforming or damaging the nail apparatus including nail bed and matrix.…”
Section: Discussionsupporting
confidence: 49%